Patterns and determinants of malaria risk in urban and peri-urban areas of Blantyre, Malawi. (December 2016) - Mathanga, Don; Tembo, Atupele; Mzilahowa, Themba; Bauleni, Andy; Mtimaukenena, Kondwani; Taylor, Terrie; Valim, Clarissa; Walker, Edward; Wilson, Mark
Abstract Background Although malaria disease in urban and peri-urban areas of sub-Saharan Africa is a growing concern, the epidemiologic patterns and drivers of transmission in these settings remain poorly understood. Factors associated with variation in malaria risk in urban and peri-urban areas were evaluated in this study. Methods A health facility-based, age and location-matched, case–control study of children 6–59 months of age was conducted in four urban and two peri-urban health facilities (HF) of Blantyre city, Malawi. Children with fever who sought care from the same HF were tested for malaria parasites by microscopy and PCR. Those testing positive or negative on both were defined as malaria cases or controls, respectively. Results A total of 187 cases and 286 controls were studied. In univariate analyses, higher level of education, possession of TV, and electricity in the house were negatively associated with malaria illness; these associations were similar in urban and peri-urban zones. Having travelled in the month before testing was strongly associated with clinical malaria, but only for participants living in the urban zones (OR = 5.1; 95% CI = 1.62, 15.8). Use of long-lasting insecticide nets (LLINs) the previous night was not associated with protection from malaria disease in any setting. In multivariate analyses, electricity in the house, travel within the previous month, and a higher level of education were all associated with decreased odds of malaria disease. Only a limited number ofAnopheles mosquitoes were found by aspiration inside the households in the peri-urban areas, and none was collected from the urban households. Conclusion Travel was the main factor influencing the incidence of malaria illness among residents of urban Blantyre compared with peri-urban areas. Identification and understanding of key mobile demographic groups, their behaviours, and the pattern of parasite dispersal is critical to the design of more targeted interventions for the urban setting.